A flavonoid-rich Smilax china L. extract prevents obesity by upregulating the adiponectin-receptor/AMPK signalling pathway and modulating the gut microbiota in mice. Issue 13 (21st May 2021) - Li, Xin; Yang, Licong; Li, Jingen; Lin, Lezhen; Zheng, Guodong
Abstract : The anti-obesity mechanism of SCF. The anti-obesity effects of SCF were possibly due to the following: (1) SCF improves lipid metabolism via adiponectin receptor/AMPK signalling; and (2) SCF modulates gut microbiota and production of SCFAs in mice. Abstract : The aim of this study was to investigate the effects of Smilax china L. flavonoid (SCF) on obesity and changes in gut microbiota high-fat/high-sucrose (HFHS)-fed mice. Male C57BL/6 mice fed either a normal-chow (NC) or a HFHS diet were treated with SCF for 12 weeks. The effect of SCF on the composition of gut microbiota was assessed by 16S rDNA sequencing. SCFA levels in the caecum were quantified by GC-MS. SCF supplementation alleviated the body weight gain, fat accumulation, serum lipid parameters, and hepatic steatosis and improved glucose homeostasis. SCF significantly increased plasma adiponectin level, adiponectin-receptor-gene (AdipoR1 and AdipoR2) expression in the liver, activated AMPKα, downregulated the expression of SREBP1-c, FAS, and ACCα, and upregulated the expression of PPARα, CPT-1α, and UCP-1. The anti-obesity effects of SCF might be through upregulation of adiponectin-receptor/AMPK signalling to improve lipid metabolism. SCF reversed HFHS-induced dysbiosis of gut microbiota and decreased SCFA production in the caecum, thus reducing energy absorption and leading to loss of body weight. Spearman's correlation analysis revealed significant correlations between obesity phenotypes, SCFA levels, and changes in gut microbiota. The results showed that SCF may be an effective dietary supplement that is useful for suppressing the development of obesity and associated disorders.